Geoscience Data and Collections: National Resources in Peril - National Research Council (The National Academies Press, 2002)
Geoscience data and collections (such as, rock and sediment cores, geophysical data, engineering records, and fossils) are necessary for industries to discover and develop domestic natural resources to fulfill the nation's energy and mineral requirements and to improve the prediction of immediate and long term hazards, such as land slides, volcanic eruptions and global climate change. While the nation has assembled a wealth of geoscience data and collections, their utility remains incompletely tapped. Many could act as invaluable resources in the future but immediate action is needed if they are to remain available. Housing of and access to geoscience data and collections have become critical issues for industry, federal and state agencies, museums, and universities. Many resources are in imminent danger of being lost through mismanagement, neglect, or disposal. A striking 46 percent of the state geological surveys polled by the committee reported that there is no space available or they have refused to accept new material. In order to address these challenges, Geoscience Data and Collections offers a comprehensive strategy for managing geoscience data and collections in the United States.
Keywords: Earth Sciences

Chemical Reference Materials: Setting the Standards for Ocean Science - National Research Council (The National Academies Press, 2002)
The accuracy of chemical oceanographic measurements depends on calibration against reference materials to ensure comparability over time and among laboratories. Several key parameters lack reference materials for measurements in seawater, particles in the water column, and sediments. Without reference materials it is difficult to produce the reliable data sets or long-term baseline studies that are essential to verify global change and oceanic stability. Chemical Reference Materials : Setting the Standards for Ocean Science identifies the most urgently required chemical reference materials based on key themes for oceanographic research and provides suggestions as to how they can be developed within realistic cost constraints. Chemical analyses of seawater are uniquely difficult given the poorly known speciation and the low concentration of many of the analytes of interest. Analyses of suspended and sedimentary marine particulate materials present their own distinct challenges, primarily due to potential interference by predominant mineral phases of different types. Of all the analytical methods applied to marine waters and particles, at present only a small fraction can be systematically evaluated via comparison to reference materials that represent the appropriate natural concentrations and matrices. Specifically, the committee was charged with the following tasks: - compile from available sources a list of important oceanographic research questions that may benefit from chemical reference standards; - create a comprehensive list of reference materials currently available for oceanographic studies; - identify and prioritize the reference materials needed to study the identified research questions; - determine for each priority analyte whether reference materials and/or analytic methods should be standardized; and - identify the most appropriate approaches for the development and future production of reference materials for ocean sciences.
Keywords: Earth Sciences; Environment and Environmental Studies

Evolutionary and Revolutionary Technologies for Mining - National Research Council (The National Academies Press, 2002)
The Office of Industrial Technologies (OIT) of the U. S. Department of Energy commissioned the National Research Council (NRC) to undertake a study on required technologies for the Mining Industries of the Future Program to complement information provided to the program by the National Mining Association. Subsequently, the National Institute for Occupational Safety and Health also became a sponsor of this study, and the Statement of Task was expanded to include health and safety. The overall objectives of this study are: (a) to review available information on the U.S. mining industry; (b) to identify critical research and development needs related to the exploration, mining, and processing of coal, minerals, and metals; and (c) to examine the federal contribution to research and development in mining processes.
Keywords: Energy and Energy Conservation; Industry and Labor

Signs of Life: A Report Based on the April 2000 Workshop on Life Detection Techniques - National Research Council (The National Academies Press, 2002)
A workshop to assess the science and technology of life detection techniques was organized by the Committee on the Origins and Evolution of Life (COEL) of the Board on Life Sciences (BLS) and the Space Studies Board (SSB). Topics discussed in the workshop included the search for extraterrestrial life in situ and in the laboratory, extant life and the signature of extinct life, and determination of the point of origin (terrestrial or not) of detected organisms.
Keywords: Space and Aeronautics

Proposed Framework for Evaluating the Safety of Dietary Supplements -- For Comment - Institute of Medicine (The National Academies Press, 2002)
Keywords: Food and Nutrition

Coal Waste Impoundments: Risks, Responses, and Alternatives - National Research Council (The National Academies Press, 2002)
On October 11, 2000, a breakthrough of Martin County Coal Corporation's coal waste impoundment released 250 million gallons of slurry in near Inez, Kentucky. The 72-acre surface impoundment for coal processing waste materials broke through into a nearby underground coal mine. Although the spill caused no loss of human life, environmental damage was significant, and local water supplies were disrupted. This incident prompted Congress to request the National Research Council to examine ways to reduce the potential for similar accidents in the future. This book covers the engineering practices and standards for coal waste impoundments and ways to evaluate, improve, and monitor them; the accuracy of mine maps and ways to improve surveying and mapping of mines; and alternative technologies for coal slurry disposal and utilization. The book contains advice for multiple audiences, including the Mine Safety and Health Administration, the Office of Surface Mining, and other federal agencies; state and local policymakers and regulators; the coal industry and its consultants; and scientists and engineers.
Keywords: Environment and Environmental Studies

Evolution of Evidence for Selected Nutrient and Disease Relationships - Institute of Medicine (The National Academies Press, 2002)
The Committee on Examination of the Evolving Science for Dietary Supplements of the Institute of Medicine's Food and Nutrition Board was directed to review, retrospectively, selected case studies of diet and health relationships that were relevant to dietary supplements and identified as important in the National Research Council report, Diet and Health: Implications for Chronic Disease Risk (D&H) (NRC, 1989). It was then to determine the extent to which subsequent scientific evidence from the peerreviewed literature used in published reports from the Dietary Reference Intakes (DRI) series (IOM, 1997, 1998, 2000a, 2001) either agreed with the preliminary evidence used to support the relationship identified originally in the 1989 review or significantly modified the original hypotheses and preliminary conclusions. The committee's analysis was to include characteristics of research with apparent high probability of predicting future confirmation by new science in support of a diet and health relationship. It also was to consider characteristics of information useful to consumers that would allow them to make scientifically informed judgments about the role that a specific food component or nutrient plays in health.
Keywords: Food and Nutrition

Sea Level Rise and Coastal Disasters: Summary of a Forum, October 25, 2001, Washington DC (The National Academies Press, 2002)
Keywords: Earth Sciences

Assessment of Proposed Partnerships to Implement a National Landslide Hazards Mitigation Strategy: Interim Report - National Research Council (The National Academies Press, 2002)
Landslides are a component of those agents of nature that transport rock and soil from mountains or hillsides to streams, lakes and seas, where new sedimentary rocks begin to form. Therefore, as well as destructive forces that can be induced by human activity, landslides are part of the earth's natural cyclic process of uplift, erosion, and sedimentation. With the growth of human population and the increasing habitation of ever-steeper slopes and higher altitudes, Man is both experiencing the effects of landslides and causing landslides with increasing frequency. These adverse effects include loss of life, injury, and damage to public and private works, as well as environmental damage. Accordingly, it is an opportune time to address the hazard posed by landslides, and to assess strategies to mitigate that hazard. Assessment of Proposed Partnerships to Implement a National Landslide Hazards Mitigation Strategy: Interim Reports is an interim statement addressing the U.S. Geological Survey's proposal for a national landslide hazards mitigation strategy. The scope of this interim report is constrained to assessing whether all the partners necessary for such a national strategy have been identified by the proposal—conclusions and recommendations to address the remainder of the statement of task will be presented in the committee's final report (e.g., will include comments regarding effective partnership implementation; funding strategies required for an effective mitigation program; and the balance between different components of a national strategy). In addition, in this interim report the committee offers a number of comments intended as interim guidance for the U.S. Geological Survey as it continues to plan a national strategy.
Keywords: Earth Sciences

High-Energy, Nutrient-Dense Emergency Relief Food Product - Institute of Medicine (The National Academies Press, 2002)
The present study was conducted by an ad hoc subcommittee of the Committee on Military Nutrition Research. The Subcommittee on Technical Specifications for a High-Energy Emergency Relief Ration was established by the Food and Nutrition Board of the Institute of Medicine in response to a request from USAID and DOD to develop technical specifications for a product for use in food relief after natural disasters or other emergency situations around the world. The specifications are to be used by both agencies in their calls for bids from U.S. food manufacturers to supply such a product.
Keywords: Food and Nutrition

Biographical Memoirs: Volume 81 - National Academy of Sciences (The National Academies Press, 2002)
Biographic Memoirs Volume 81 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

The Quarantine and Certification of Martian Samples - National Research Council (The National Academies Press, 2002)
One of the highest-priority activities in the planetary sciences identified in published reports of the Space Studies Board's Committee on Planetary and Lunar Exploration (COMPLEX) and in reports of other advisory groups is the collection and return of extraterrestrial samples to Earth for study in terrestrial laboratories. In response to recommendations made in such studies, NASA has initiated a vigorous program that will, within the next decade, collect samples from a variety of solar system environments. In particular the Mars Exploration Program is expected to launch spacecraft that are designed to collect samples of martian soil, rocks, and atmosphere and return them to Earth, perhaps as early as 2015.International treaty obligations mandate that NASA conduct such a program in a manner that avoids the cross-contamination of both Earth and Mars. The Space Studies Board's 1997 report Mars Sample Return: Issues and Recommendations examined many of the planetary-protection issues concerning the back contamination of Earth and concluded that, although the probability that martian samples will contain dangerous biota is small, it is not zero.1 Steps must be taken to protect Earth against the remote possibility of contamination by life forms that may have evolved on Mars. Similarly, the samples, collected at great expense, must be protected against contamination by terrestrial biota and other matter. Almost certainly, meeting these requirements will entail opening the sample-return container in an appropriate facility on Earth-presumably a BSL-4 laboratory-where testing, biosafety certification, and quarantine of the samples will be carried out before aliquots are released to the scientific community for study in existing laboratory facilities. The nature of the required quarantine facility, and the decisions required for disposition of samples once they are in it, were regarded as issues of sufficient importance and complexity to warrant a study by the Committee on Planetary and Lunar Exploration (COMPLEX) in isolation from other topics. (Previous studies have been much broader, including also consideration of the mission that collects samples on Mars and brings them to Earth, atmospheric entry, sample recovery, and transport to the quarantine facility.) The charge to COMPLEX stated that the central question to be addressed in this study is the following: What are the criteria that must be satisfied before martian samples can be released from a quarantine facility?
Keywords: Space and Aeronautics

Riparian Areas: Functions and Strategies for Management - National Research Council (The National Academies Press, 2002)
The Clean Water Act (CWA) requires that wetlands be protected from degradation because of their important ecological functions including maintenance of high water quality and provision of fish and wildlife habitat. However, this protection generally does not encompass riparian areas—the lands bordering rivers and lakes—even though they often provide the same functions as wetlands. Growing recognition of the similarities in wetland and riparian area functioning and the differences in their legal protection led the NRC in 1999 to undertake a study of riparian areas, which has culminated in Riparian Areas: Functioning and Strategies for Management. The report is intended to heighten awareness of riparian areas commensurate with their ecological and societal values. The primary conclusion is that, because riparian areas perform a disproportionate number of biological and physical functions on a unit area basis, restoration of riparian functions along America's waterbodies should be a national goal.
Keywords: Earth Sciences; Environment and Environmental Studies

Analysis of Engineering Design Studies for Demilitarization of Assembled Chemical Weapons at Blue Grass Army Depot - National Research Council (The National Academies Press, 2002)
The U.S. Army is in the process of destroying the nation's stockpile of aging chemical weapons stored at eight locations in the continental United States and on Johnston Atoll in the Pacific. Originally, incineration was chosen for the destruction of these stores, but this method has met with public opposition, and Congress directed the Army to develop alternative technologies for destroying the stockpiles in Pueblo, CO and Richmond, KY. To assist the Army in this process, the NRC was asked to evaluate the engineering design study of the three Blue Grass candidates. This book presents an analysis of various issues pertaining to the proposed engineering design package for the Blue Grass facility.
Keywords: Environment and Environmental Studies; Math, Chemistry, and Physics

Review of NASA's Earth Science Enterprise Applications Program Plan (The National Academies Press, 2002)
Keywords: Space and Aeronautics; Earth Sciences

Research Opportunities in Geography at the U.S. Geological Survey - National Research Council (The National Academies Press, 2002)
Research Opportunities in Geography at the U.S. Geological Survey (USGS) provides perspective and guidance to the geography discipline about its future research and strategic directions. The book makes specific recommendations about scientific research priorities and partnerships within and outside the agency, and outlines a long-term core research agenda for the USGS.
Keywords: Earth Sciences

Remedial Action at the Moab Site: Now and for the Long Term: Letter Report - National Research Council (The National Academies Press, 2002)
Keywords: Environment and Environmental Studies

The Scientific Basis for Estimating Air Emissions from Animal Feeding Operations: Interim Report - National Research Council (The National Academies Press, 2002)
This is an interim report of the ad hoc Committee on Air Emissions from Animal Feeding Operations of the National Research Council's Committee on Animal Nutrition. A final report is expected to be issued by the end of 2002. The interim report is intended to provide the committee's findings to date on assessment of the scientific issues involved in estimating air emissions from individual animal feeding operations (swine, beef, dairy, and poultry) as related to current animal production systems and practices in the United States. The committee's final report will include an additional assessment within eight broad categories: industry size and structure, emission measurement methodology, mitigation technology and best management plans, short- and long-term research priorities, alternative approaches for estimating emissions, human health and environmental impacts, economic analyses, and other potential air emissions of concern.This interim report focuses on identifying the scientific criteria needed to ensure that estimates of air emission rates are accurate, the basis for these criteria in the scientific literature, and uncertainties associated with them. It also includes an assessment of the emission-estimating approaches in a recent U.S. Environmental Protection Agency (EPA) report Air Emissions from Animal Feeding Operations. Finally, it identifies economic criteria needed to assess emission mitigation techniques and best management practices.
Keywords: Agriculture; Environment and Environmental Studies

Safe on Mars: Precursor Measurements Necessary to Support Human Operations on the Martian Surface - National Research Council (The National Academies Press, 2002)
This study, commissioned by the National Aeronautics and Space Administration (NASA), examines the role of robotic exploration missions in assessing the risks to the first human missions to Mars. Only those hazards arising from exposure to environmental, chemical, and biological agents on the planet are assessed. To ensure that it was including all previously identified hazards in its study, the Committee on Precursor Measurements Necessary to Support Human Operations on the Surface of Mars referred to the most recent report from NASA's Mars Exploration Program/ Payload Analysis Group (MEPAG) (Greeley, 2001). The committee concluded that the requirements identified in the present NRC report are indeed the only ones essential for NASA to pursue in order to mitigate potential hazards to the first human missions to Mars.
Keywords: Space and Aeronautics

Down to Earth: Geographic Information for Sustainable Development in Africa - National Research Council (The National Academies Press, 2002)
In 1992, world leaders adopted Agenda 21, the work program of the 1992 U.N. Conference on Environment and Development. This landmark event provided a political foundation and action items to facilitate the global transition toward sustainable development. The international community marked the tenth anniversary of this conference in Johannesburg, South Africa, in August 2002. Down to Earth, a component of the U.S. State Department's "Geographic Information for Sustainable Development" project for the World Summit, focuses on sub-Saharan Africa with examples drawn from case-study regions where the U.S. Agency for International Development and other agencies have broad experience. Although African countries are the geographic focus of the study, the report has broader applicability. Down to Earth summarizes the importance and applicability of geographic data for sustainable development and draws on experiences in African countries to examine how future sources and applications of geographic data could provide reliable support to decision-makers as they work towards sustainable development. The committee emphasizes the potential of new technologies, such as satellite remote-sensing systems and geographic information systems, that have revolutionized data collection and analysis over the last decade.
Keywords: Earth Sciences; Environment and Environmental Studies